Perlindungan Data Pribadi Dalam Kasus Kebocoran Digital (Tinjauan Hukum Pidana Terhadap Platform Digital) - Nurasih, Moch Joko; Dhumillah, Dewic Sri Ratnaning (Postulat, 2026)
Technological developments are leading society toward greater sophistication, offering various efficiencies. While digital platforms are certainly helpful to various segments of society, they can also be detrimental if used without proper oversight. This means that technological advancements must be accompanied by legal developments to minimize actions detrimental to society, in this context, regarding data leaks that frequently occur on digital platforms. This study aims to analyze whether criminal law provisions regulate the accountability of digital platform operators in cases of personal data leaks, and to analyze the effectiveness of criminal sanctions in handling data leak cases. This type of research is conceptual normative legal research, with literature review as a data collection tool. Based on the research results, Law No. 27 of 2022 concerning Personal Data Protection regulates criminal law provisions within the framework of personal data protection. However, law enforcement in the context of personal data protection still faces obstacles. On the other hand, minimizing personal data leaks is a collective responsibility between the government, platform owners, and the public. Therefore, good cooperation between these three elements is necessary to ensure efficient personal data protection.